Net Endogenous Acid Excretion and Kidney Allograft Outcomes. Issue 9 (September 2021) - Yeung, Stanley M.H.; Gomes-Neto, Antonio W.; Osté, Maryse C.J.; van den Berg, Else; Kootstra-Ros, Jenny E.; Sanders, Jan Stephan F.; Berger, Stefan P.; Carrero, Juan Jesus; De Borst, Martin H.; Navis, Gerjan J.; Bakker, Stephan J.L.
Visual Abstract: Abstract : Background and objectives: High dietary acid load may accelerate a decline in kidney function. We prospectively investigated whether dietary acid load is associated with graft outcomes in kidney transplant recipients, and whether venous bicarbonate mediates this association. Design, setting, participants, & measurements: We used data from 642 kidney transplant recipients with a functioning graft ≥1 year after transplantation. Net endogenous acid production was estimated using food frequency questionnaires and, alternatively, 24-hour urinary urea and potassium excretion to estimate net endogenous acid production. We defined the composite kidney end point as a doubling of plasma creatinine or graft failure. Multivariable Cox regression analyses, adjusted for potential confounders, were used to study the associations of dietary acid load with the kidney end point. We evaluated potential mediation effects of venous bicarbonate, urinary bicarbonate excretion, urinary ammonium excretion, titratable acid excretion, and net acid excretion on the association between net endogenous acid production and the kidney end point. Results: The median net endogenous acid production using food frequency questionnaires and net endogenous acid production using urinary excretion were 40 (interquartile range, 35–45) and 54 (interquartile range, 44–66) mEq/day, respectively. During a median follow-up of 5.3 years (interquartile range, 4.1–6.0), 121 (19%) participants reached the kidney end point. After multivariable adjustment, net endogenous acid production using food frequency questionnaires and net endogenous acid production using urinary excretion (per SD higher) were independently associated with higher risk for kidney end point (hazard ratio, 1.33; 95% confidence interval, 1.12 to 1.57, P =0.001 and hazard ratio, 1.44; 95% confidence interval, 1.24 to 1.69, P <0.001, respectively). Baseline venous bicarbonate mediated 20% of the association between net endogenous acid production using food frequency questionnaires and the kidney end point. Baseline venous bicarbonate, urinary ammonium excretion, and net acid excretion mediated 25%, −14%, and −18%, respectively, of the association between net endogenous acid production using urinary excretion and the kidney end point. Conclusions: Higher dietary acid load was associated with a higher risk of doubling of plasma creatinine or graft failure, and this association was partly mediated by venous bicarbonate, urinary ammonium, and net acid excretion.